Application of Artificial Gastrointestinal Tract Models in Veterinary Medicine - Sergei Konstantinovich Shebeko; Heorhii Yurievich Drobot; Andrey Georgievich Koshchaev; Svetoslav Dimitrov Todorov; Alexey Mikhailovich Ermakov (Animals)
Artificial gastrointestinal tract models have become essential tools in veterinary medicine, providing alternatives to in vivo studies, which are labor-intensive, costly, and under certain circumstances even ethically challenging. These in vitro models facilitate the study of digestion, enable disease and host–pathogen interaction modeling, and allow for the investigation of nutrient absorption, microbiota, and pharmacokinetics. Considering the One Health concept, the application of gastrointestinal tract systems in investigations for animals can clearly reflect human health, and thus, it is pointing to the relevance of the adaptation of already existing models and the development of new models to meet the needs of veterinary and animal farming practices. This review explores and compares the various types of gastrointestinal tract models, including static and dynamic systems, and their applications across different animal species. Specific technical and methodological considerations are discussed for core animal-developed and -tested artificial systems and their integration with common ‘omics’ techniques. Dynamic models, such as RUSITEC and PolyFermS, more accurately simulate in vivo processes, including peristalsis, enzymatic activity, and microbial fermentation. The studies employing tools for ‘omics’ approaches have been conducted with more understanding analysis and comprehensive discussion and results.